Study of the Tourism Destination Image Formation Process and the Factors Affecting It - abolfazl taj zadeh namin; garigur ghazarian (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2010)
Tourism Destination Image (TDI) has an essential role and impact on the tourist' decision making process, destination selection and the tourists behavior. The present article is an attempt to give a holistic view on the image, it’s process, and the important factors affecting the image formation (either before or after visiting a destination). The results indicate that the image formation is affected by the tourist’s perception and personality, as well as the destination profile. It is hoped that this article will be useful as a guide for destination marketing and planning.